Frequency of Oral Mucosal Lesions and Awareness of these Lesions in Patients Attending Oral and Maxillofacial Clinic in Sari Dental School, Iran - Tahereh Molania; Azam Nahvi; Mohammmadsharif Delrobaee; Maede Salehi (Journal of Mazandaran University of Medical Sciences, 2017)
Background and purpose: There are considerable differences in prevalence of oral lesions in different parts of the world.  Few studies are done on this problem in Iran, so this study aimed at investigating the prevalence of oral lesions and awareness of these lesions in patients attending Oral and Maxillofacial Clinic in Sari Dental School, Iran.